2021
DOI: 10.48550/arxiv.2104.13977
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spectrally peaked proton beams shock accelerated from an optically shaped overdense gas jet by a near-infrared laser

Abstract: We report on the generation of impurity-free proton beams from an overdense gas jet driven by a near-infrared laser (λ L = 1.053 µm). The gas profile was shaped prior to the interaction using a controlled prepulse. Without this optical shaping, a (30 ± 4) nC sr −1 thermal spectrum was detected transversely to the laser propagation direction with a high energy (8.27 ± 0.07) MeV, narrow energy spread ((6 ± 2) %) bunch containing (45 ± 7) pC sr −1 . In contrast, with optical shaping the radial component was not d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…For near infra-red lasers (λ 0 1 μm), the derived values of a 0 correspond to intensities between 1.3 × 10 18 -2.7 × 10 20 W cm −2 , which could be achieved at current laser facilities. Indeed electrostatic shocks have been driven with these lasers in highly pressurised gas jets [45,[47][48][49] or tailored solid targets [46]. In order to launch two counterpropagating shocks, two lasers or one laser split into two pulses using a technique similar to that described in [72] could be used to illuminate two frontal targets or the opposite sides of the same target.…”
Section: Experimental Perspectivesmentioning
confidence: 99%
See 2 more Smart Citations
“…For near infra-red lasers (λ 0 1 μm), the derived values of a 0 correspond to intensities between 1.3 × 10 18 -2.7 × 10 20 W cm −2 , which could be achieved at current laser facilities. Indeed electrostatic shocks have been driven with these lasers in highly pressurised gas jets [45,[47][48][49] or tailored solid targets [46]. In order to launch two counterpropagating shocks, two lasers or one laser split into two pulses using a technique similar to that described in [72] could be used to illuminate two frontal targets or the opposite sides of the same target.…”
Section: Experimental Perspectivesmentioning
confidence: 99%
“…Ions at rest are reflected by the electrostatic potential of the shock to twice the shock velocity, making the electrostatic shock an efficient mechanism for particle acceleration. The generation of electrostatic shocks in laser-driven plasmas and the production of high-quality proton beams have now been demonstrated in several experiments [41][42][43][44][45][46][47][48][49]. Computer simulations performed under realistic experimental conditions revealed that a shock is launched when the radiation pressure exerted by the laser steepens the plasma density and creates a density spike and, at the same time, target electrons are heated to high temperatures, such that T e T i , with T e and T i electron and ion temperatures, respectively [50][51][52].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kordell et al [23] used a cryogenically cooled supersonic Ar/H gas jet with a knife edge to modify the density profile of the gas jet. Hicks et al [24] used a high pressure hydrogen gas jet to reach high densities, and additionally formed a blast wave using a lower power prepulse to produce a sharp density gradient on axis, similar to the work of Helle et al [25]. Chen et al used an extremely high pressure hydrogen gas jet [26], similar to that characterized by Sylla et al [27].…”
Section: Introductionmentioning
confidence: 98%